Clinical Outcomes of Propolis-Supplemented Therapies in Verruca Vulgaris: A Prospective Observational Study - Huseynova, Chinara; Yücesoy Sera Nur; Kutlubay, Zekayi (Cerrahpaşa Medical Journal, 2025)
Objective: Verruca vulgaris is a common infectious dermatosis for which treatment alternatives have gained importance. In this study, the aim was to evaluate the efficacy of systemic propolis, an alternative treatment modality, when used with both destructive treatments and topical propolis, and to monitor the recurrence in the long term. Methods: This study is a prospective study that included 58 patients with verruca vulgaris. Of the 58 patients, 20 received electrocauterization with propolis supplementation, 21 received cryotherapy with propolis supplementation, and 17 received propolis cream with propolis supplementation. Results: The decrease in the number of lesions in the 3 treatment groups was statistically significant in the third and sixth months compared to pretreatment. The total cure rates of the patient groups at the third and sixth months were 35% and 70% in the cryotherapy + oral propolis group, 42% and 71% in the electrocauterization + oral propolis group, and 29% and 41% in the propolis cream + oral propolis group, respectively. The main limitations of this study are small sample size and lack of control group. Conclusion: This study suggests that oral propolis supplementation, when combined with destructive or topical treatments, appears to improve treatment outcomes and may help reduce recurrence. While these findings are encouraging, the absence of a control group and the inability to isolate the effect of oral propolis alone warrant cautious interpretation. Further randomized controlled trials with larger populations are needed to confirm the efficacy and safety of propolis in verruca vulgaris. Cite this article as: Huseynova C, Yücesoy SN, Kutlubay Z. Clinical outcomes of propolis-supplemented therapies in verruca vulgaris: a prospective observational study. Cerrahpaşa Med J. 2025, 49, 0031, doi: 10.5152/cjm.2025.25031.